Overlapping - Oded Stark; Yong Wang (University of Bonn, Center for Development Research (ZEF), 2002)
We propose a new microeconomic explanation for the divergent experiences of economies in forming human capital. We suggest that the positive effect of a longer life expectancy on human capital formation arises from two separate effects: a life expectancy effect and a prolonged intergenerational overlap effect. We argue that the duration of the overlap between generations and the associated parental support can affect the marginal cost of human capital formation and hence its level: parental support is cheaper than market financing. We thus attribute the strong correlation between the formation of human capital and life expectancy not merely to a higher marginal benefit arising from a longer payback period but also to a lower marginal cost arising from a prolonged intergenerational overlap. We provide conditions under which a longer overlap results in a higher level of per capita output.
Keywords: 330; Labor and Human Capital; Bildungsinvestition; Bildungsertrag; Generationengerechtigkeit; Sterblichkeit; Overlapping Generations; Wohlfahrtsanalyse; Theorie